Charged space debris induced nonlinear magnetosonic waves using inertial magnetohydrodynamics. Issue 11 (1st June 2022) - Acharya, Siba Prasad; Mukherjee, Abhik; Janaki, M.S.
Abstract: The excitations of nonlinear magnetosonic waves in the presence of charged space debris objects in the low Earth orbital (LEO) plasma region are investigated by taking into account the effects of electron inertia in the framework of classical magnetohydrodynamics (MHD); which is also referred to as inertial magnetohydrodynamics. The magnetosonic waves are found to be governed by a forced Kadomtsev–Petviashvili (KP) equation with the forcing term representing the effects of space debris objects. The dynamical behaviours of both slow and fast magnetosonic solitary waves are explored in detail. Exact pinned accelerated magnetosonic lump wave solutions are shown to be stable for the entire region in the parameter space of slow waves and a large region in the parameter space of fast waves. In a similar way, exact pinned curved magnetosonic solitary wave solutions become stable for a small region in the parameter space of fast waves. These exact solutions with special properties are derived for some specific choices of the forcing debris functions. These novel results can have potential applications in the scientific and technological aspects of the space debris detection and mitigation in the near-Earth space.